The Impact of Qur’anic Reading and Listening Duration and Frequency on Cognitive Performance and Hippocampal Function: A Systematic Review - Rahmi, Upik; Putri, Suci Tuty; Fitriana, Lisna Anisa; Murtiani, Farida (IIUM Medical Journal Malaysia, 2026)
Engaging with the Qur'an, whether through reading or listening, necessitates complex cognitive processing of the written or spoken Arabic language. This activity demands concentration and attention, thereby engaging cognitive functions such as selective attention, Arabic language processing, and auditory perception. The purpose of this paper is to review the effects of reading and listening to the Qur'an on hippocampal cognitive function. A literature search was conducted using online databases: ScienceDirect, PubMed/ Medline, and Scopus. The keywords used in the literature search were “cognitive”, “Qur'an”, and “hippocampus”. This approach included six full-length articles. A manual search of the cited references was also used to find additional considerations for the discursive analysis of each topic discussed in this review. As a sacred text, the Qur'an engages both reading and listening skills and involves cognitive processes that impact memory and comprehension. Regular engagement with the Qur'anic text and its recitation can significantly improve brain activity, memory, and cognitive development. Reading and listening are essential skills for language comprehension and communication. When a person reads the Qur'an, he or she engages in visual Arabic language processing, while when listening to its recitation, the person is involved in auditory language processing. These activities stimulate different parts of the brain, contributing to a more comprehensive understanding of the Qur'an text.